Bifunctionality of dirhodium tetracarboxylates in metallaphotocatalysis - Taoda Shi; Tianyuan Zhang; Jiying Yang; Yukai Li; Jirong Shu; Jingyu Zhao; Mengchu Zhang; Dan Zhang; Wenhao Hu (Nature Communications, 2023)
Abstract Metallaphotocatalysis has been recognized as a pivotal catalysis enabling new reactivities. Traditional metallaphotocatalysis often requires two or more separate catalysts and exhibits flaw in cost and substrate-tolerance, thus representing an await-to-solve issue in catalysis. We herein realize metallaphotocatalysis with a bifunctional dirhodium tetracarboxylate ([Rh2]) alone. The [Rh2] shows an photocatalytic activity of promoting singlet oxygen (1O2) oxidation. By harnessing its photocatalytic activity, the [Rh2] catalyzes a photochemical cascade reaction (PCR) via combination of carbenoid chemistry and 1O2 chemistry. The PCR is characterized by high atom-efficiency, excellent stereoselectivities, mild conditions, scalable synthesis, and pharmaceutically interesting products. DFT calculations-aided mechanistic study rationalizes the reaction pathway and interprets the origin of stereoselectivities of the PCR. The products show inhibitory activity against PTP1B, being promising in the treatment of type II diabetes and cancers. Overall, here we show the bifunctional [Rh2] merges Rh-carbenoid chemistry and 1O2 chemistry.